2022
DOI: 10.36513/sigma.v8i1.1533
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Modul Berbantuan Geogebra Pada Matakuliah Kalkulus Integral Lipat

Abstract: The lack of interaction between students and lecturers in learning causes information not to be conveyed optimally. Moreover, fold integral calculus is an abstract material. Therefore, learning innovations are applied that can support more independent learning and are able to visualize abstract material. This study aims to determine the feasibility of the geogebra-assisted electronic module in the fold integral calculus course. This research is classified as development research which refers to Sugiyono develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The significance of this result was in line with the research conducted by Rifa'I and Nisa' (2019) stating that emodules could increase student learning independence in calculus material. In addition, Meilasari & Khotimah (2022) revealed that e-modules might improve learning students' outcomes in folding integral calculus topics.…”
Section: B Discussionmentioning
confidence: 99%
“…The significance of this result was in line with the research conducted by Rifa'I and Nisa' (2019) stating that emodules could increase student learning independence in calculus material. In addition, Meilasari & Khotimah (2022) revealed that e-modules might improve learning students' outcomes in folding integral calculus topics.…”
Section: B Discussionmentioning
confidence: 99%
“…Apriliyani (2022), developed an interactive e-module based on geogebraassisted guided discovery learning that is valid, practical and effective for understanding the concept of flat-sided shapes for class VIII SMP students. Meilasari and Khotimah (2022), developed a foldable integral calculus e-module which was made suitable for use by 72.4% of students achieving optimal learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%